(untitled) (Географический вестник=Geographical bulletin, 2017)
Рассматривается влияние разработки месторождений соли и гипса на ландшафты Богдинско-Баскунчакского района. Предложены меры для предотвращения негативного антропогенного воздействия в данном районе. INFLUENCE OF MODERN TECHNOGENESIS ON LANDSCAPES OF BOGDINSKO-BASKUNCHAKSKIY DISTRICT OF ASTRAKHAN REGION In given article influence of working out of deposits of salt and plaster on landscapes of Bogdinsko-Baskunchakskiy district is considered. Also measures for prevention of negative anthropogenous influence in the given area are resulted.